Analisis Pelaksanaan Program Sekolah Ramah Anak di Surabaya: Studi pada SDN KEDUNGDORO V dalam Menciptakan Lingkungan Sekolah yang Bebas Kekerasan Fisik dan Bullying - Reza Maharani Putri Tizaka; Hasan Ismail (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
Violence in children is a problem that often occurs in units of education. To solve this problem, the government made new policies, namely the Children's Friendly School policy. The policy aims to protect all the rights of children in Indonesia created by the Ministry of Women's Empowerment and Child Protection of the Republic of Indonesia. This study aims to analyze the implementation of the Child-Friendly School Program (SRA) at SDN Kedungdoro V Surabaya by focusing on the creation of a free school environment from physical violence and bullying. In the context of Indonesia's education, SRA implementation is considered important to ensure children's rights that are guaranteed and protected, and are protected from the discriminatory situation of violence and treatment. This research uses a qualitative descriptive approach with primary data from interviews and observation results. The results suggested that the SDN Kedungdoro V Surabaya had implemented SRA with reference to the Minister of PPPA Regulation Number 8 of 2014. However, obstacles arise regarding resources, especially in terms of financial resources and time. Although there is a positive increase in the behavior of teachers and students, the incidence of bullying is still happening. The results of this study indicate that resource variables still need improvement in their management. In the coordination variables between the implementing agency have been running well, but it is necessary to improve in terms of optimal time allocation. However, the SRA program in the school has had a positive impact on the school environment and student active participation.